Advanced molecular plant breeding : meeting the challenge of food security - Bharadwaj, D. N. (Dinesh Narayan) (Oakville, ON, Canada ; Waretown, NJ, USA : Apple Academic Press Inc., 2019)
"This new volume provides a better understanding of molecular plant breeding in order to boost the quality of agriculture produce, to increase crop yields and to provide nutritious food for everyone by 2050. Scientists believe the challenge can be met by implementing new and improved techniques of quantitative trait inheritance in plant breeding. Integrating genomics and molecular biology into appropriate tools and methodologies can help to create genetically engineered plants, such as by using biotic and abiotic stress tolerance, molecular markers, '-omics' technology, and genome editing."--Provided by publisher.
Sustainable agriculture and food security : 2050 (future plant breeding) / D.N. Bharadwaj -- Application of genotype and environmental interactions in plant breeding / Chandra Nath Mishra, Satish Kumar, K. Venkatesh, Vikas Gupta, Devmani Bind, and Ajay Verma -- Forward and reverse genetics in plant breeding / Masochon Raingam, Megha Bhatt, Akash Sinha, and Pushpa Lohani -- Biodiversity and conservation of plant genetic resources (in-situ and ex-situ) / Sheel Yadav, Chet Ram, and Dhammaprakash Pandhari Wankhede -- Uses and importance of wide hybridization in crop improvement / Vikas Gupta, Chandra Nath Mishra, and Satish Kumar -- Application of mutation breeding in plants / A.K. Mehta and M.H. Basha -- Applications of molecular marker-assisted breeding in plants / S. Pandey and V.C. Pandey -- Importance of genomic selection in crop improvement and future prospects / Satish Kumar, Senthilkumar K. Muthusamy, Chandra N. Mishra, Vikas Gupta, and Karnam Venkatesh -- Application and achievements of recombinant DNA technology in crop improvement / Rakesh Kumar, H.M. Mamrutha, Karnam Venkatesh, Kashi Nath Tiwari, and Satish Kumar -- Plant tissue culture techniques and its achievements / S. Pandey and V.C. Pandey -- Breeding strategies to convert C3 plants into C4 plants / Akshaya Kumar Biswal, Arun Kumar Singh, Vivek Thakur, Satendra Kumar Mangrauthia, and Revathi Ponnuswamy -- Molecular pharming (pharmaceuticals) : primary and secondary metabolites in plants / Mir Zahoor Gul, Mohd Yasin Bhat, Anirudh Kumar, and Beedu Sashidhar Rao -- Plant-based edible vaccines : an innovative concept to immunization / Rajeev Sharma, Nishi Mody, and Suresh P. Vyas -- Breeding for nutritional quality enhancement in crops : biofortification and molecular farming / Rahul Priyadarshi, Hitendra Kumar Patel, and Anirudh Kumar -- Terminator technology (GURT technology) / D.R. Mehta and A.K. Nandha -- Omics in plant breeding / D.R. Mehta and Ramesh Kumar -- RNA interference (RNAI) technology in biology and plant breeding / Dinesh Narayan Bharadwaj -- Genome editing in plant breeding / D.R. Mehta and A.K. Nandha -- Nanobiotechnology in agriculture / D.N. Bharadwaj and Sanjay Kumar Singh.
OCLC-licensed vendor bibliographic record.
Keywords: Plant genetic engineering; Plant breeding; Crops -- Genetic engineering; TECHNOLOGY & ENGINEERING / Agriculture / General; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / Biology / Molecular Biology; TECHNOLOGY / Agriculture / General